The bandwidth dilemma applied to trait emotional intelligence: comparing the contribution of emotional intelligence factor with its facets for predicting global job satisfaction - Rodrigues, Nuno (2022)
Building upon the relevance of emotional intelligence (EI) in influencing key attitudes at work, the current study aimed to compare the contribution of the trait-EI factor with its specific facets for predicting overall job satisfaction. Relying on a concurrent design, results from a sample of 228 software engineers from a multi-national firm showed that trait-EI global factor remained a significant and non-redundant predictor of this attitudinal criterion, even when the big five are also taken into consideration. Results also revealed that corresponding facets of self-emotions appraisal, other-emotions appraisal, use of emotion, and regulation of emotion, when residualized (i.e., their factor variance is partialed out), do not outperform the contribution of the higher-order trait-EI factor and the big five in the prediction of overall job satisfaction. Theoretical and practical implications of these results are discussed.